Examining the effects of psychiatric symptoms, brain injury symptoms, and low self-control on the placement of inmates in administrative segregation and their risk for suicidal ideation - Chintakrindi, Sriram (Array, 2021)
Objective: In this study, we are interested in understanding the predictive effects of psychiatric symptoms, brain injury symptoms, and criminological factors on inmate (N=270) risk for placement in administrative segregation and their expression of suicidal ideation. Methods: Using a case-control design, this study seeks to understand the psychological and behavioral risk-profiles of inmates being placed in administrative segregation and those with suicidal ideation. More specifically, we are trying to understand the magnitude of the effect that psychiatric symptoms, brain injury symptoms, and low self-control characteristics has on the risk of inmates being placed in administrative segregation and their risk for suicidal ideation. Results: We found that factor scores for psychiatric symptoms and low self-control levels significantly increase the risk of inmates expressing suicidal ideation when compared to alternative predictive factors.